Growth of Rubber Seeds (Hevea brasiliensis Muell.Arg) from Sleeping Eye Stum by Applying Organic Fertilizer Bulk and Liquid Herbal Waste - Fahrizal Fahrizal; Rusli Anwar; Jamaluddin; Muhamad Yazid Bustomi (Jurnal Loupe, 2024)
The organic fertilizer derived from herbal medicine waste in both bulk and liquid form is rich in macro and micro nutrients as well as decomposing microbes and probiotic bacteria needed to improve soil chemical properties.  These fertilisers can be used to obtain better growth of rubber seedlings, especially rubber seedlings of sleeping eye origin. The objectives of this study was(1) to determine the effect of organic fertilizer and liquid bulk herbs Against Waste growth and (2) to know nutrient uptake of N, P, and K seedling stum Sleep eye. The study was conducted in a 4 x 3 factorial experiment arranged in a completely randomized design (CRD) with five replications. The first factor is the concentration of organic liquid fertilizer consisting of four in the standard: h0 = 0 ml L-1 of air (0%); h1 = 2 ml L-1 air (0.2%); h2 = 4ml L-1 air (0.4%); h3 = 6ml L-1 air (0.6%). The second factor is the dose of organic fertilizer consists of three levels: (b0 = 0 mg ha-1: b1 = 5 mg ha-1: b2 = 10 Mg ha-1). Data were analyzed with Analysis of Variant and continued with Duncan's Multiple Range Test 5% level. The results showed that the dosage of bulk organic fertilizers was significantly different at the level of 5% of the uptake of nitrogen, other observations were not significantly different. While the treatment of liquid organic fertilizer was highly significantly different at the level of 1% of nitrogen absorption, other observations were not significantly different. No real effect on their interaction in all observations. The treatment dose of organic fertilizer 5 Mg ha-1 and the treatment of liquid organic fertilizer 4 ml L-1 provided the highest results in leaf area of 586.46 cm2 per plant compared to the control treatment of 181.06 cm2 per plant. The treatment of bulk organic fertilizer dose and liquid organic fertilizer concentration predicted P2O5 nutrient uptake per rubber plant did not show significant differences. While the treatment of doses of bulk organic fertilizer and concentrations of liquid organic fertilizer is thought to be potassium nutrient uptake per rubber plant does not show significant differences, but can be seen from the growth of diameter, number of leaves, and leaf area.